An advanced review of speech-languaje pathology - Rose-McKibbin, Celeste; Hegde, M. N. (United States : Pro-ed, 2006)
The idea for the first of this book was born in 1996 was part of a team that was conducting workshops for speech-languaje pathologists who needed to pass the PRAXIS so the could become license and certified in order to accommodate increasingly profesional state and federal requirements.
Contensts Chapter I : Anatomy, Neuroanatomy and physiology of the speech mechanismo Chapter 2 Physiological and acoustic phonetics: A specch science foundation Chapter Languaje development in children
Contiene index
Keywords: LANGUAJE PATHOLOGY; PATHOLOGY; PATOLOGÍA DEL LENGUAJE